2014
DOI: 10.1016/j.earlhumdev.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The case for quality improvement in the Neonatal Intensive Care Unit

Abstract: Quality improvement (QI) is now a central part of the work of clinicians throughout healthcare. It is based on clear scientific principles, a valid way of measuring change and has theories of reliability and human factors that underpin the interventions. The Neonatal Intensive Care Unit (NICU) is a highly complex adaptive system that lends itself to the application of QI principles. This will require the development of a safety culture that continually seeks to improve. Clinicians and all those who work in NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Such a multifactorial strategy can be achieved through the quality improvement concept of ‘care bundle’. Care bundle approaches in NICUs have been reported to reduce catheter-related sepsis, retinopathy of prematurity or to improve neonatal pain management [10]. Very recently, such a ‘care bundle’ strategy to adhere to a nutrition protocol has also been described as a very effective approach for improving linear and head circumference growth, reducing postnatal growth restriction, and decreasing comorbidities (necrotizing enterocolitis, sepsis) in very low birth weight (<1500 g) infants [11].…”
Section: Implementation Strategies and Long-term Outcome Studies Amentioning
confidence: 99%
“…Such a multifactorial strategy can be achieved through the quality improvement concept of ‘care bundle’. Care bundle approaches in NICUs have been reported to reduce catheter-related sepsis, retinopathy of prematurity or to improve neonatal pain management [10]. Very recently, such a ‘care bundle’ strategy to adhere to a nutrition protocol has also been described as a very effective approach for improving linear and head circumference growth, reducing postnatal growth restriction, and decreasing comorbidities (necrotizing enterocolitis, sepsis) in very low birth weight (<1500 g) infants [11].…”
Section: Implementation Strategies and Long-term Outcome Studies Amentioning
confidence: 99%
“…The use of core outcome sets for trials is promoted by journals,18 Cochrane Review Group editors19 and research funders 20. Relevant, standardised outcomes are also crucial for observational research,21 22 benchmarking,23 clinical audit24 and quality improvement studies 25…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinearity designates that repetition of the same issue can lead to different outcomes . Many authors in their research view health care organizations as CAS . Sturmberg et al suggested a complex health care system model for understanding health system reform.…”
Section: Introductionmentioning
confidence: 99%
“…10,13 Many authors in their research view health care organizations as CAS. 12,[14][15][16][17][18][19] Sturmberg et al 20 suggested a complex health care system model for understanding health system reform. Sarriot and Kouletio 12 found that health systems, through complex adaptive behaviours, achieved sustainable outcomes.…”
mentioning
confidence: 99%